Lease financing mechanism for scaling up SMEs for expansion of pit emptying service delivery in low income areas; Perspectives from of Lusaka, Zambia - Pride Kafwembe; Yvonne Siyeni (2022)
A conference contribution for the 1st Water-WISER Early Career Researcher Conference, Transdisciplinary Global Perspectives on Water and Waste Services, held at Loughborough University 21 - 23 June 2022.